2014
DOI: 10.5005/jp-journals-10024-1621
|View full text |Cite
|
Sign up to set email alerts
|

Early and Immediate Loading Protocols for Overdentures in Completely Edentulous Maxillas: A Comprehensive Review of Clinical Trials

Abstract: A comprehensive review was conducted to answer the question 'Does the immediate loading of dental implants with an overdenture in the maxilla provide predictable clinical and psychological outcomes?' Detailed search strategies were used to identify pertinent articles in English that were published between 1975 and August 2013 and indexed in PubMed, MEDLINE, Embase, The Cochrane Central Register of Controlled Trials, and a personal library; in addition, relevant journals were manually searched. Only randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
(70 reference statements)
1
6
0
Order By: Relevance
“…The variation in ISQ values is reflective of the biologic changes at the bone implant interface. This finding is similar to (27,28) The results from our study concluded that there is statistically significant difference between the control and test groups; p=0.02. The mean primary implant stability of group A (osteotome) was 6.3±7.2 compared to 66.0±8.8 in group B (densah bure).…”
Section: Discussionsupporting
confidence: 87%
“…The variation in ISQ values is reflective of the biologic changes at the bone implant interface. This finding is similar to (27,28) The results from our study concluded that there is statistically significant difference between the control and test groups; p=0.02. The mean primary implant stability of group A (osteotome) was 6.3±7.2 compared to 66.0±8.8 in group B (densah bure).…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, many other different studies reported insignificant difference between immediate and delayed loading of dental implants (43)(44)(45)(46)(47)(48) .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, excessive force concentration in a particular area of the superstructure or prosthesis should be avoided. Bone resorption may occur when excessive stress loads are applied to the supporting bone, and if left unattended implant failure could follow [1,7,19]. Also, when extra stresses are applied to the implant fixtures and or the superstructure components, prosthetic complications-such as screw loosening or screw fracture or fracture of the abutments, etc.-could occur [36,42,48,[50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Maxillary implant-retained overdentures are considered a favorable treatment option for patients with insufficient bone volume, retention, and stability complaints [1][2][3][4][5][6][7]. However, a consensus is lacking regarding the adequate number of implants necessary to support a maxillary overdenture or the different anchorage systems used [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%